(untitled) (Biological Sciences - PJSIR, 2001)
River Niger, the largest river in Nigeria flows southwards across Asaba and Onitsha to the Delta areas. The clarins buthopogon (fish) and Nymphaea lotus (aquatic plant) from the River Niger at Asaba were sampled for analysis using Atomic Absorption Spectrophotometer (AAS). The concentration of the heavy metals from the three parts of the fish (head, muscle and tail) had the following ranges: Cr, 8.90-9.70; Cu, 2.90-3.90; Fe, 6.00-113.20; Mg, 138.00-3398; Ni, 5.48-14.68; Pb, 0.20-1.60; Hg, 0.38-2.00 and Cd, 1.41-1.78 mg kg’ on dry weight basis. These values were higher than those obtained in Kaduna River and Mediterranean coaster waters. The concentrations in Nymphaea Lotus (aquatic plant) were extremely high (Cr, 20.30; Cu, 10.70; Fe, 569.20; Mg, 6798.00; Ni, 72.08; Pb, 6.00; Hg, 51.30 and Cd, 31.10 mg kg:’ dry weight) and were also higher than those of fish part The bioaccumulation of heavy metals in fish parts and aquatic plant indicated pollution, as per WHO and FEPA standards for aquatic life.